Sustainable Strategies to Prevent Iron Deficiency, Improve Yield and Berry Composition in Blueberry (Vaccinium spp.) - Michel, Lucía; Peña, Álvaro; Pastenes, Claudio; Berríos, Pablo; Rombolà, Adamo Domenico; Covarrubias, José Ignacio (Frontiers in Plant Science, 2019)
The aim of this investigation was to study the effect of sustainable strategies to correct iron deficiency in blueberries, based on Fe-heme applications or intercropping with graminaceous species, on yield, and berry quality variables. The experiment was conducted in a blueberry orchard established in a sub-alkaline soil. The association with grasses increased the crop load and yield (only Festuca rubra), and decreased the skin/flesh ratio. In addition, these treatments increased anthocyanins as well as some hydroxybenzoic acids, hydroxycinnamic acids, flavanols, and flavonol concentrations in skins with a similar effectiveness as Fe-EDDHA, whereas the Fe-heme applications did not influence such parameters. Moreover, data revealed that the association with both grasses decreased the firmness of the berries, whereas none of the treatments assessed changed the soluble solids, pH, acidity, and the soluble solids/acidity rate compared to the control. These results suggest that Fe nutrition is crucial for yield and berry quality in blueberry, and that intercropping with grasses may be an effective and sustainable alternative to counteract Fe deficiency in blueberry, with a similar effect on berries to that achieved with Fe-EDDHA.